Case report: Spontaneous lens absorption after the implantation of an implantable collamer lens - Liu, Xiaojing; Zeng, Qiulin; Lu, Ting; Wang, Min; Sun, Yong; Zhang, Jingfa (Frontiers in Medicine, 2023)
BACKGROUND Spontaneous lens absorption is rare, usually happening in eyes with some syndromes, hyper-mature cataract and ocular trauma. Implantation of implantable collamer lens (ICL) is widely performed in patients with high myopia for refractive correction. In this study, a case of lens spontaneous absorption after ICL implantation was reported. CASE SUMMARY A 23-year-old male was referred with complaint of poor vision in his left eye. The patient underwent binocular ICL implantation for refractive correction of high myopia 1.5 years ago. Ten months later, he experienced sudden visual loss and pain in the left eye, which was relieved spontaneously next day without any treatment. Since then, the visual acuity of his left eye decreased gradually. At presentation, slit-lamp examination revealed ICL in the posterior chamber in both eyes; while, in the left eye, the anterior capsular fibrotic proliferation, posterior capsular opacity, and the residual cortex of lens sandwiched between the anterior fibrotic membrane and the opacified posterior capsule were evidenced. The number of corneal endothelial cells was 1,337 in his left eye, which was less than that before ICL implantation (2,902). The patient was then underwent the ICL extraction, anterior capsular capsulotomy, residual cortex aspiration, posterior capsular polishing, and intraocular lens implantation. CONCLUSION Spontaneous absorption of lens might happen in patients with ICL implantation. The patients should underwent routine follow-up after ICL implantation.